Aviation Cyber Security in India: Legal Gaps, International Frameworks, and Policy Reforms - Mohammad Owais Farooqui; Adnan Sarhan; Faizan Mustafa (Yustisia, 2025)
Large passenger data breaches, ransomware attacks, and politically motivated Distributed Denial of Service attacks show that aviation faces cyber dangers to safety, national security, and consumer confidence. This article examines India's aviation cybersecurity governance, evaluates legal culpability in cyber incidents, and proposes worldwide best practices-based reforms. This study uses doctrinal and analytical legal methods. This study compares ICAO, EU, and US international frameworks, notably NIS2 and GDPR, to aviation and cybersecurity statutes, regulations, policy papers, and judicial interpretations. The findings reveal that India has fundamental cyber and data protection laws but no aviation-specific cybersecurity policies, unambiguous liability allocation, or strong enforcement. Institutional fragmentation and resource constraints increase these risks. Comparing India to other countries shows it violates worldwide laws, emphasising the need for accountability, supervision, and cyber risk management changes in the aviation sector. India can improve resilience, foster a proactive security culture, and assure passenger trust and operational safety in the digital age by following ICAO regulations and EU and US best practices